Loss of Krüppel-like factor 3 (KLF3/BKLF) leads to upregulation of the insulin-sensitizing factor adipolin (FAM132A/CTRP12/C1qdc2) - Bell-Anderson, Kim S.; Funnell, Alister P.; Williams, Helen; Mat Jusoh, Hanapi; Scully, Tiffany; Lim, Wooi; Burdach, Jon; Mak, Ka Sin; Knights, Alexander; Hoy, Andrew; Nicholas, Hannah R.; Sainsbury, Amanda; et al. (American Diabetes Association, 2013)
Krüppel-like factor 3 (KLF3) is a transcriptional regulator that we have shown to be involved in the regulation of adipogenesis in vitro. Here, we report that KLF3-null mice are lean and protected from diet-induced obesity and glucose intolerance. On a chow diet, plasma levels of leptin are decreased, and adiponectin is increased. Despite significant reductions in body weight and adiposity, wild-type and knockout animals show equivalent energy intake, expenditure, and excretion. To investigate the molecular events underlying these observations, we used microarray analysis to compare gene expression in Klf3(+/+) and Klf3(-/-) tissues. We found that mRNA expression of Fam132a, which encodes a newly identified insulin-sensitizing adipokine, adipolin, is significantly upregulated in the absence of KLF3. We confirmed that KLF3 binds the Fam132a promoter in vitro and in vivo and that this leads to repression of promoter activity. Further, plasma adipolin levels were significantly increased in Klf3(-/-) mice compared with wild-type littermates. Boosting levels of adipolin via targeting of KLF3 offers a novel potential therapeutic strategy for the treatment of insulin resistance.